Predication of Drug Target Interaction using Reliable Multicast Routing in Wireless Ad hoc Molecular Network - Gopinath, S.; Murugan, K. (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Wireless Ad hoc Molecular network consists of atoms in terms of nodes in the absence of administrative point. In this connection, there is a need to adopt molecular analogy to define the architecture. Prediction of Drug Target Interaction (DTI) is a major impact in molecular ad hoc network. Efforts were made to combine such information with data to define DTI and to construct biological space. The concept of Conditional Random Field (CRF) is used in our proposed reliable multicast routing to integrate genomic, chemical and functional data to predict DTI. Reliability of links was also maintained to increase the network performance. Based on the extensive simulation results, the proposed reliable routing protocol achieves better performance than existing schemes.